(untitled) (Revista Internacional de Folkcomunicação, 2024)
The work presented is part of an extensive work, within which it acquires another meaning than the one it has here. For this occasion, it has a sense of openness, and presentation of the spiritual aesthetic dimension, of what I call the history of liberation (see bibliography Bauer, Carlos: 2015, 2016, 2021, 2022, 2024). Therefore, this writing proposes a spiritual path of entry into the history of liberation (to reconstruct one of its keys and excluded dimensions), at the same time, indicating the aesthetic path, as access to the spiritual dimension. It is not the only path, there are others, but it is the one that in this case is explained here. The objective is to achieve an integrated and organic vision of history, with its fundamental social-spiritual mission, constituted as history for liberation.